ПРОСТОРОВО-ЧАСОВА МІНЛИВІСТЬ СТРУКТУРИ ПРИБЕРЕЖНОГО ЦИЛІАТОПЛАНКТОНУ В ОДЕСЬКІЙ ЗАТОЦІ ЧОРНОГО МОРЯ - Курілов, О. В. (Marine Ecological Journal, 2023)
The peculiarities of the spatial distribution of structural components of the ciliatoplankton community in coastal areas of the Odessa Bay have been considered. It is shown that traverses and breakwaters, affecting the degree of closeness of the water areas, as well as depth and amount of hard substrates in basins, have a marked influence on the species richness, diversity and, to a lesser extent, on the abundance and biomass of planktonic ciliates. The trophic structure formed by species composition and also by changes of the food situation was slightly different in the study areas. Both trophic structure and the abundance/biomass were the least informative indicators. The size structure was different in the study areas, but its formation mechanisms are intricate and require further study based on other components of the biota such as periphyton and zooplankton. Most of the differences in the structure of ciliatoplankton of the examined basins are most clearly seen on a background of unstable temperature conditions. A detailed analysis of the entire set of structural characteristics allowed to select representative areas according to the integrated environmental factors impact on coastal ciliatoplankton of the Odessa Bay.